Kinerja Pegawai Universitas Lampung Ditinjau dari Gaya Kepemimpinan dan Motivasi VASI KERJA - Apandi Apandi; Yulianto Yulianto; Feni Rosalia (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2019)
The purpose of this study was to determine the performance of Lampung University employees, through leadership style and work motivation. This study used a correlational quantitative approach. The population of this study was all employees of education staff at the General and Financial Devision at Lampung University of 110 people. Samples were taken purposively, as many as 53 employees. Data was collected using survey methods. The data were analyzed by simple and multiple linear regression with the help of SPSS 17.0 statistical software. Based on the results of testing the hypothesis of the influence of leadership style on employee performance, the results of t-count of 2.374 and t-table of 1.67655 were obtained. Furthermore, the motivation variables on employee performance, the results of t-count were 7.283 and t-table was 1.67655. Simultaneous testing or jointly obtained results of F-count statistics of 40,288 and F-table 3.18. The results of the analysis can be concluded that employee performance at the General and Financial Bureau of Lampung University is influenced by motivation.